16S rRNA Gene-targeted TTGE in Determining Diversity of Gut Microbiota during Acute Diarrhoea and Convalescence (Journal of Health, Population and Nutrition, 2012)
The human gut microbiota play a vital role in health and nutrition but are greatly modified during severe  diarrhoea due to purging and pathogenic colonization. To understand the extent of loss during and after  diarrhoea, faecal samples collected from children (n=21) suffering from acute diarrhoea and from their  healthy siblings (n=9) were analyzed by 16S rRNA gene-targeted universal primer polymerase chain reaction  (PCR), followed by temporal temperature gradient gel electrophoresis (TTGE). The gut microbiota  decreased significantly as indicated by the number of TTGE bands at day 0 of acute diarrhoea [patients vs  healthy siblings: 11±0.9 vs 21.8±1.1 (mean±standard error), p